Response to Lefebvre et al. Issue 5 (9th October 2017) - Takeda, K.; Kou, I.; Kawakami, N.; Yasuhiko, Y.; Ogura, Y.; Imagawa, E.; Miyake, N.; Matsumoto, N.; Sudo, H.; Kotani, T.; ,; Nakamura, M.; et al.
Abstract : Congenital scoliosis (CS) is a common vertebral malformation with incidence of up to 1 of 1000 births worldwide. Recently, TBX6 has been reported as the first disease gene for CS: about 10% of CS patients are compound heterozygotes of rare null mutations and a common haplotype composed by 3 SNPs in TBX6. Lefebvre et al in this journal reported that 2 patients with spondylocostal dysostosis (SCD), a rare skeletal dysplasia affecting spine and ribs also have TBX6 mutations: 1 carried the microdeletion and a rare missense variant, and another 2 rare missense variants. We investigated the pathogenicity of the 3 missense variants in SCD by a luciferase assay. The results were negative for the proposal of Lefebvre et al. We consider these 2 SCD patients are more probably compound heterozygotes of null mutations and a common risk haplotype just as CS patients with TBX6 mutations.